Držení těla a funkční stav pohybového aparátu u dětí ve věku 6-8 let: případová studie - Šeráková, Hana (Tělesná výchova a výchova ke zdraví, 2022)
Title in English: Posture and muscle imbalances in children aged 6-8 years: case study The monograph focuses on the posture of children aged 6-8, specifically on the period before they enter the primary school and on the first two years of schooling. In six case studies, we focus on the quality of posture, the functional state of selected muscles and muscle groups of the monitored children and their physical activity regime. In order to examine the musculoskeletal system, we use visual methods and functional muscle test by Janda, and we also use observation, interview, questionnaire survey and other methods. The findings of the original research provide detailed knowledge regarding posture, the state of the musculoskeletal system and the locomotor regime of children at school and outside, which partly differ from other authors' findings.